Conflict of Interest and the Credibility of Underwriter Analyst Recommendations - Michaely, Roni; Womack, Kent L. (Review of Financial Studies, 1999)
Brokerage analysts frequently comment on and sometimes recommend companies that their firms have recently taken public. We show that stocks that underwriter analysts recommend perform more poorly than “buy” recommendations by unaffiliated brokers prior to, at the time of, and subsequent to the recommendation date. We conclude that the recommendations by underwriter analysts show significant evidence of bias. We show also that the market does not recognize the full extent of this bias. The results suggest a potential conflict of interest inherent in the different functions that investment bankers perform.